Report on improving smallholder women farmers’ access to finance for small-scale irrigation technologies - Feed the Future Innovation Lab for Small Scale Irrigation (Feed the Future Innovation Lab for Small Scale Irrigation, 2023)
Widespread use of small power pumps in South Asia has revolutionized agricultural production since the 1970s. In the past few years, solar photovoltaic pumps have become affordable alternatives to diesel and grid-powered electric pumps. While their initial investment is higher, the near-zero operating costs make them extremely attractive (Xie et al. 2021; Lefore et al. 2021). They have additional benefits, including reducing the national fuel import bill; and producing no greenhouse gases. Small solar-powered pumps are portable and can be used for many purposes. India, among others, is investing billions of Indian Rupees in subsidies to ramp up their use; and partnerships among private firms, NGOs, governments, researchers, and investors are trying to expand their uptake in sub-Saharan Africa. A major downside is that most irrigation pumps are being acquired by relatively wealthy male farmers, exacerbating already high levels of inequality in rural communities. Poor smallholders, especially women, cannot meet the required credit checks and therefore cannot purchase the pumps. Nor do they have access to finance to purchase complementary inputs such as fertilizer and seeds. In response, various research institutions, pump manufacturers, and NGOs are exploring how to target irrigation pumps to poor smallholders, women, and youth. Many studies and pilot programs have been implemented and shown positive results. The challenge is to scale out the successful pilots based on lessons learned. This brief explores the lessons learned and identifies potential ways forward.